A Review of Different Polymer and Plasticizers - Gita Sahu (International Journal of Membranes, 2024)
Plasticizer and polymer are essential components in the pharmaceutical industry, especially when creating both cutting-edge and conventional drug delivery systems. The differences between synthetic, semi-synthetic, and all-natural polymers are examined in this review to highlight their diverse qualities and uses. When designing drug delivery systems to target areas, the choice of polymer is crucial. Because of their repeatability and adaptability, synthetic polymers are widely used in the creation of precision medication delivery systems. Certain polymers, such poly (lactic-co-glycolic acid) (PLGA) and polyethylene glycol (PEG), are well-known for their tunable characteristics and biocompatibility, which makes them appropriate for targeted drug release. Semi-synthetic polymers, on the other hand, provide a medium between regulated drug release and biodegradability, bridging the gap between natural and fully synthetic materials. This class of cellulose derivatives includes, for example, hydroxypropyl methylcellulose (HPMC), which is helpful in the formulation of medications with a variety of release characteristics. Plasticizers are an essential component that is used for coating tablets and maintaining medication release. They ensure the best possible medication delivery by improving the polymeric coatings' flexibility and durability. Common plasticizers that affect the final dosage form's mechanical and release qualities are triethyl citrate (TEC) and dibutyl phthalate (DBP). The usage of polymers and plasticizers has several disadvantages notwithstanding their benefits. Drug stability or efficacy may be changed by interactions between polymers and pharmaceuticals. Furthermore, some plasticizers may show signs of toxicity, which means that pharmaceutical formulations must undergo careful testing and adhere to regulations. The discovery of novel pharmacological remedies is the aim of this comprehensive study. Through clarifying the fundamental properties of polymers, classifying different kinds, and describing the roles of plasticizers, scientists may better customise drug delivery systems. The assessment highlights the significance of giving considerable thought and optimisation to reduce harmful effects while addressing potential issues.
Keywords: GA; PVP; Plasticizers; Synthetic; natural; polymer